GAMBARAN FAKTOR-FAKTOR YANG MEMPENGARUHI GANGGUAN TAJAM PENGLIHATAN PADA ANAK SEKOLAH DASAR KELAS V DAN KELAS VI DI SDN 017 BUKIT RAYA PEKANBARU TAHUN 2014 - Juneti "; Eka Bebasari; Efhandi Nukman (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Vision screening recommended to detect tampering visual acuity at school age.gender, academic achievement, play activities, family history of glasses and nutritional statusis one of the risk of sharp vision disorders. purpose of this study to determine visual acuitydisturbances. This is a descriptive study with cross-sectional research design and totalsampling techniques has been done in september 2014. Snellen card and the questionnairequestions of the schedule of activities performed during the 3 days are used for data retrievalfor 1 hour / day. most respondents have normal vision with the best visual acuity 83.76%. theresults of this study showed the most characteristic sex is women (68.42%), academicachievement (38.47%), activity play (81.58%), look close and long activity that most peopledo is read near as many as 16 people (42.1%) with a close distance ≤ 30cm and  2hours/day, watching tv as many as 18 people (47.36%) at a distance of 3 times the diagonallength of the tv and  2 hours/day, using a computer, notebook, playstation / video games asmany as 16 people (42.1%) at a distance ≤ 50cm and  2 hours/day. family history of glassesage  40 years and nutritional status (63.2%).Keyword: visual acuity disorders, elementary school kids, factor affected visual disorders